Mikropropagacija koščičarjev - Šiško , Metka (University of Maribor Press, 2022)
Micropropagation of Stone Fruits. Micropropagation is the basic technique of plant tissue cultures. It is a method of rapid vegetative propagation of plants in the laboratory. Propagation of woody plants by micropropagation is in most cases much more difficult than micropropagation of herbaceous plants. The most difficult is the first stage of micropropagation, where we disinfect plant material. In the case of trees growing outdoors, we can also encounter internal infections that cannot be removed by surface sterilization methods. For woody plants, the rooting stage can also be difficult. Each genotype has its own requirements, so we need to study the optimal procedure for each one. At the Faculty of agriculture and life sciences at the University of Maribor, we have been working on the successful propagation of stone fruits in vitro for several years. Most studies are done on apricots, cherries and plums, so the micropropagation of these species is described in more detail in the publication. The first part of the publication is an overview of the individual stages of micropropagation, including a description of the laboratory and the necessary equipment for working with tissue cultures. The publication will also serve as teaching material for students in subjects of plant biotechnology and plant tissue cultures.